CONSTRUCTING FEMINISTS MAPS OF GOIÂNIA CITY - Cabral, Talita (Revista Eletrônica: Tempo - Técnica - Território / Eletronic Magazine: Time - Technique - Territory, 2018)
The goal is to construct maps of feminists actions in Goiania(GO). The chosen methodology use stories of leadership, by means of semi structured interviews with thirteen feminists and the interactive mapping techniques. Were mapped the places and routes considerate important in the woman fight.